Design and Analysis of conveyor chain link using composite material: a Review - Amol J. Kadam; Dr. Shailesh V. Deshpande (International Journal of Innovations in Engineering Research and Technology, 2021)
The basic aim of this review has been conducted on the most of the time conveyor chain is under tension which causes failure of chain assembly which is the major problem for industrial sector. Causes of this failure are improper design. It is important to study the influence of these parameters. All these parameters can be considered simultaneously and chain link design optimally. Optimization is the process of obtaining the best result under given circumstances in design of system. In optimization process we can find the conditions that give the maximum and minimum value of function.In this study a shape optimization process is used for the design of roller chain link for minimization of failure modes.